Taxpayer Compliance Based on Tax Socialization Mediated by Taxpayer Awareness: Behavioral Approach - Farida Styaningrum; Ahmad Nur Aziz; Nik Amah; Zainul Khoirunnisa; Anggita Putri Pramudyawati (Jurnal Dinamika Akuntansi, 2025)
Purposes: The purpose of the research is to test a taxpayer compliance model where taxpayer awareness mediates the tax socialization they receive. The research results provide strategic policy recommendations to the government regarding effective tax socialization to build voluntary compliance.Methods: The population is MSME taxpayers registered at KPP Pratama Madiun. A sample of 130 respondents was obtained through incidental sampling. Data collection used a questionnaire-based survey filled out by Micro, Small, and Medium Enterprises (MSMEs) actors. Smart Partial Least Square (Smart-PLS) to analyze mediation regression models. The relationship between variables is explained using a behavioral theory approach.Findings: Socialization increases taxpayer compliance directly and through taxpayer awareness. These results strengthen the government's efforts to increase taxpayer awareness through quality, effective, intensive, and sustainable tax socialization and education. Taxpayer awareness is expected to encourage voluntary compliance.Novelty: Similar studies have been conducted before, but not for MSMEs in Madiun City. We include the indicator of “compliance in reporting Tax Returns (SPT)” which is often overlooked by other studies in measuring taxpayer compliance. Several groups of MSMEs with income below a certain limit are not required to pay taxes but are still required to report SPT.